2013
DOI: 10.1016/j.jphotobiol.2013.09.010
|View full text |Cite|
|
Sign up to set email alerts
|

Transfection of pseudouridine-modified mRNA encoding CPD-photolyase leads to repair of DNA damage in human keratinocytes: A new approach with future therapeutic potential

Abstract: UVB irradiation induces harmful photochemical reactions, including formation of cyclobutane pyrimidine dimers (CPDs) in DNA. Accumulation of unrepaired CPD lesions causes inflammation, premature ageing and skin cancer. Photolyases are DNA repair enzymes that can rapidly restore DNA integrity in a light-dependent process called photoreactivation, but these enzymes are absent in humans. Here, we present a novel mRNA-based gene therapy method that directs synthesis of a marsupial, Potorous tridactylus, CPD-photol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 58 publications
2
29
0
2
Order By: Relevance
“…Such interactions seem to play a crucial role in amino acylation fidelity and efficiency in yeast (52) where ⌿ interactions with adenosine strengthen the anticodon-codon/stop codon interactions (51,53,54). These findings might explain why incorporation of pseudouridine into mRNA makes it highly stable and translatable, offering a number of opportunities for medical applications (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such interactions seem to play a crucial role in amino acylation fidelity and efficiency in yeast (52) where ⌿ interactions with adenosine strengthen the anticodon-codon/stop codon interactions (51,53,54). These findings might explain why incorporation of pseudouridine into mRNA makes it highly stable and translatable, offering a number of opportunities for medical applications (9).…”
Section: Discussionmentioning
confidence: 99%
“…Pseudouridine, which has been found in the functionally important regions of RNAs (5), is known to modulate codon-anticodon interactions between mRNA and tRNA (6) and assist assembly of the ribosome (7) and spliceosome (8). The presence of pseudouridine in mRNA makes the message non-immunogenic and highly translatable, thus offering therapeutic opportunities in medical applications (9).…”
mentioning
confidence: 99%
“…A Potorous tridactylus fotoliáz génjét kódoló mRNS-t kollaboráció keretében Karikó Katalin laboratóriuma in vitrotranszkripcióval hozta létre. A szekvencia kodon-optimalizálásával, az mRNS pszeudouridin-módosításával, hosszú poly(A) farok és cap1 struktúra kialakításával, valamint az mRNS HPLC tisztításával összességében magas transzlációs hatékonyságot, és biológiai stabilitást sikerült elérni, amit a DE OEC Bôrgyógyászati Klinika kutatócsoportja igazolt (34). Kísérleteink elsô fázisában kimutattuk, hogy a transzfektált, majd fotoreaktivált humán keratinocitákban a CPD-k száma több mint 60%-kal csökkent a fotoliáz aktivációjához szükséges energiaforrást nélkülözô sejtekhez képest, ami bizonyította, hogy a transzlált fehérje funkcionálisan is aktív.…”
Section: Nukleozid-módosított Fotoliáz Mrns In Vitro Vizsgálatai éS Aunclassified
“…Kísérleteink elsô fázisában kimutattuk, hogy a transzfektált, majd fotoreaktivált humán keratinocitákban a CPD-k száma több mint 60%-kal csökkent a fotoliáz aktivációjához szükséges energiaforrást nélkülözô sejtekhez képest, ami bizonyította, hogy a transzlált fehérje funkcionálisan is aktív. A fotoreaktivá-ció szignifikánsan csökkentette az UVB dózis antiproliferatív hatását (34). A fotoliáz mRNS keratinocitákba juttatása alkalmasnak tûnik az UVB-indukálta CPD léziók eltávolítására humán keratinocitákban, ami elôrevetíti alkalmazási lehetôségét a bôrdaganatok megelôzésében.…”
Section: Nukleozid-módosított Fotoliáz Mrns In Vitro Vizsgálatai éS Aunclassified
“…15,41 A prominent example is a C residue in eukaryotic U2 RNA that stabilizes and fine-tunes spliceosomal branchsite interaction 39,173 , involving a water-CNH1 hydrogen bond. 174,175 Functional importance for RNA C in artificial mRNAs Synthetic replacement of all uridines by C renders mRNAs non-immunogenic 176 , increases biological stability [176][177][178] and enhances translation in vivo 176,179,180 , while reducing PKR activation. 181 In contrast, studies with in vitro assays suggested that mRNAs where all Us were changed to Cs inhibit translation at the initiation and elongation levels.…”
mentioning
confidence: 99%